STANDAR MUTU PENDIDIKAN, TEMUAN DAN SOLUSI MUTU DI ERA NEW NORMAL - Abdul Mujib; Muhammad Rudi Wijaya (Roqooba Journal of Islamic Education Management, 2022)
The impact of the Covid-19 pandemic has caused a decrease in the quality of education which has an impact on educational output and outcomes. Strategies and policies at the micro, meso, and macro levels are needed to improve the quality and performance of the education ecosystem in schools. Therefore National policies are important so that they become a common concern in responding to the declining quality of education in the new normal life with strategic regulations and policies that can form quality outputs that are met by stakeholders.Education is an asset of a nation, therefore special attention is needed in efforts to improve the quality of education. The government as the party that plays the most role in the world of education should always strive to continuously improve the quality of education in Indonesia with breakthroughs or new programs.Quality assurance can be applied in education (schools), where the school seems to be a separate system of context, input, process, output, outcome (short term impact and long term impact), where the focus of quality assurance lies on the input. The targets of quality assurance activities in the education sector are the stages:input, process, outcome, and impact. Targets in education include: student selection and qualitycurriculum, facilities and infrastructure, teachers, and supporting staff, learning and assessmentprocesses, competency of graduates, alumni and stakeholders, and academic management